2018
DOI: 10.1007/s00246-018-1868-x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Trabecular Formation and Specification During Cardiogenesis

Abstract: Trabecular morphogenesis is a key morphologic event during cardiogenesis and contributes to the formation of a competent ventricular wall. Lack of trabeculation results in embryonic lethality. The trabecular morphogenesis is a multistep process that includes, but not limited to, trabecular initiation, proliferation/growth, specification and compaction. Although a number of signaling molecules have been implicated in regulating trabeculation, the cellular processes underlying mammalian trabecular formation are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 67 publications
0
37
0
Order By: Relevance
“…In the embryonic zebrafish heart, a subpopulation of cardiomyocytes residing in the compact myocardium begin to extend distinct protrusions before a directional migration into the trabecular layer leading to trabeculae formation (Liu et al, 2010; Staudt et al, 2014). A similar paradigm was reported in the mammalian embryonic heart as trabecular formation involves the directional migration of a subpopulation of cardiomyocytes that undergo cytoskeleton rearrangement, become elongated, orient perpendicular to the compact myocardium, and migrate into the cardiac jelly (Samsa et al, 2013; Wu, 2018). Two independent studies reported that nestin was expressed in mouse embryonic cardiomyocytes during cardiogenesis and the present study revealed that de novo nestin expressed in NNVMs was associated with a migratory phenotype (Meus et al, 2017; Kachinsky et al, 1995).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…In the embryonic zebrafish heart, a subpopulation of cardiomyocytes residing in the compact myocardium begin to extend distinct protrusions before a directional migration into the trabecular layer leading to trabeculae formation (Liu et al, 2010; Staudt et al, 2014). A similar paradigm was reported in the mammalian embryonic heart as trabecular formation involves the directional migration of a subpopulation of cardiomyocytes that undergo cytoskeleton rearrangement, become elongated, orient perpendicular to the compact myocardium, and migrate into the cardiac jelly (Samsa et al, 2013; Wu, 2018). Two independent studies reported that nestin was expressed in mouse embryonic cardiomyocytes during cardiogenesis and the present study revealed that de novo nestin expressed in NNVMs was associated with a migratory phenotype (Meus et al, 2017; Kachinsky et al, 1995).…”
Section: Discussionmentioning
confidence: 69%
“…The migration of mononucleated cardiomyocytes also constitutes a prerequisite event during the formation of the embryonic heart. In the embryonic zebrafish and mammalian heart, trabecular formation was initiated by cardiomyocytes that undergo cytoskeleton rearrangement, become elongated, orient perpendicular to the heart wall, and eventually migrated into the cardiac jelly (Liu et al, 2010; Samsa, Yang, & Lui, 2013; Staudt et al, 2014; Wu, 2018). In the embryonic zebrafish heart, several studies have reported that before trabeculae formation, cardiomyocytes begin to extend distinct protrusions (Liu et al, 2010; Staudt et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second concept of the formation of myocardial trabeculae describes the emergence and expansion of the trabecular layer of the embryonic ventricles as a centripetal growth process [100,113,116,117,118]. This means that the myocardial trabeculae are suspected to elongate by inward growth toward the centers of the embryonic ventricles (see Figure 3 in [100], Figure 3 in [116], and Figure 1 in [117]).…”
Section: Morphology and Function Of The Cj During The Advanced Phamentioning
confidence: 99%
“…1 in [112]). This inward growth is suspected to result either from a buckling process [95] or from the translocation of ventricular cardiomyocytes (by directional cell migration and oriented cell divisions) into non-removed CJ between the endocardial projections of the trabecular shields [reviewed by Wu 2018]. The latter mechanistic concept suggests that the CJ might act as a physical route for the ingrowth of myocardial trabeculae.…”
Section: Notes On Ventricular Trabeculation and Ballooningmentioning
confidence: 99%